Efecto de los ácidos humicos como promotores de la productividad primaria en el cultivo de camaron en churute provincia del Guayas - Niola Mora, Hermes Edison (2012)
The present research tried to establish the effect of humic acids as promoters of primary productivity, using three doses of the product. The study was done on site group shrimp Samaniego Angel located in Churute Guayas Province. The research had three replicates with an average amount of 19 976 cells / ml for treatment 1, 27 009 cells / ml for treatment 2 and 36 402 cells / ml. For treatment 3, the witness 19022 cells / ml. Samples were taken weekly to control weight gain, dosage balanced food and shrimp health. The variables studied were quantified weekly phytoplankton cells / ml, weekly shrimp growth in grams, expressed in% final survival, production expressed in lb / ha and feed conversion in pounds of balanced vs. consumed. Pounds of shrimp produced. And the final results indicate no significant difference for any treatment, however treatment three reached numerically better results in terms of production in pounds per acre and higher weekly counting phytoplankton cells / ml must conclude that treatment with a dose three 1.5 liters per hectare of humic acid is more effective that resulted.